Association of renal impairment with cognitive dysfunction in the Northern Ireland Cohort for the Longitudinal Study of Ageing (NICOLA) - Paterson, Euan N (Nephrol Dial Transplant, 2021)
INTRODUCTION: Chronic kidney disease (CKD) is a recognized risk factor for cognitive impairment. Identification of those at greatest risk of cognitive impairment may facilitate earlier therapeutic intervention. This study evaluated associations between estimated glomerular filtration rate (eGFR) and cognitive function in the Northern Ireland Cohort for the Longitudinal Study of Ageing. METHODS: Data were available for 3412 participants ≥50 years of age living in non-institutionalized settings who attended a health assessment between February 2014 and March 2016. Measures of serum creatinine (SCr) and cystatin C (cys-C) were used for eGFR. Cognitive function was measured using the Montreal Cognitive Assessment (MoCA) and the Mini-Mental State Examination (MMSE). RESULTS: Following adjustment for potential confounders, a single unit decrease in eGFR was significantly associated with reduced cognitive function defined by an MMSE ≤24/30 {eGFR calculated using serum cys-C [eGFRcys]: β = −0.01 [95% confidence interval (CI) −0.001 to −0.01], P = 0.01} and MoCA <26/30 [β = −0.01 (95% CI −0.002 to −0.02), P = 0.02]. Similarly, CKD Stages 3–5 were also associated with a moderate increase in the odds of cognitive impairment (MMSE ≤24) following adjustment for confounders [eGFRcys: odds ratio 2.73 (95% CI 1.38–5.42), P = 0.004]. CONCLUSIONS: Decreased eGFRcys was associated with a significantly increased risk of cognitive impairment in a population-based cohort of older adults. However, there was no evidence of an association between cognitive impairment and the more commonly used eGFR calculated using SCr. eGFRcys may offer improved sensitivity over eGFRcr in the determination of renal function and associated risk of cognitive impairment.